Development of historical immersive learning media to strengthening Pancasila Student Profiles in vocational high school - Nugroho, Alifi Nur Prasetia (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
This study aims to develop historical immersive learning media to improve the Pancasila student profiles in Vocational High Schools (SMK) in Indonesia. This research and development use ADDIE's research steps method (analyze, design, develop, implement, and evaluate). The results show that immersive learning media can enhance the understanding and appreciation of Pancasila values among SMK students. The media effectively stimulates students' interest in history and encourages them to apply Pancasila values daily. The study concludes that immersive learning media can potentially strengthen the Pancasila student profiles and promote the development of responsible, tolerant, and patriotic citizens in Indonesia. The result of media tests on vocational students obtained satisfactory results, with the average overall score reaching 4.25 or in the category of "Very Decent."  The findings suggest that implementing immersive learning media in SMKs should be encouraged and supported by policymakers, educators, and other stakeholders in the education sector.